Antimicrobial packaging based on ɛ‐polylysine bioactive film for the control of mycotoxigenic fungi in vitro and in bread. Issue 1 (9th June 2017) - Luz, C.; Calpe, J.; Saladino, F.; Luciano, Fernando B.; Fernandez‐Franzón, M.; Mañes, J.; Meca, G.
Abstract: ɛ‐Poly‐l‐ lysine (ɛ‐PL) is a cationic peptide with a broad‐spectrum antimicrobial activity. This study investigates the use of ɛ‐PL as natural antimicrobial to inhibit fungal growth and to reduce aflatoxins (AFs) production. Antifungal activity of starch biofilms with different concentrations of ɛ‐Poly‐l‐ lysine (ɛ‐PL) was determined in solid medium against Aspergillus parasiticus (AFs producer) and Penicillium expansum . Then, biofilms were tested as antimicrobial devices for the preservation of bread loaf inoculated with A. parasiticus CECT 2681 and P. expansum CECT 2278. Shelf life and AFs content were examined. Biofilms with concentrations of ɛ‐PL less than 1.6 mg/cm 2 showed no fungal growth inhibition in solid medium, while the antifungal activity of the films with greater than 1.6 mg/cm 2 of ɛ‐PL was dose dependent. The shelf life of bread inoculated with A. parasiticus was increased by 1 day with the use of films containing 1.6–6.5 mg ɛ‐PL/cm 2, while shelf life of bread tainted with P. expansum was increased by 3 day with 6.5 mg ɛ‐PL/cm 2 . AFs production was greatly inhibited by ɛ‐PL biofilms (93–100%). Thus, ɛ‐PL biofilms could be potentially used as antimicrobial device during bread storage as a natural alternative to the synthetic preservatives. Practical applications: Ɛ‐Polylysin is a natural substance from microbial metabolism. Polylysine has a function to prevent a microbe from proliferating by ionic adsorption in the microbe. ɛ‐polylysine has a wide antibacterial spectrum and has an obvious lethal effect on Gram‐positive and Gram‐negative bacteria, yeast, mold, viruses, etc. It has a good antibacterial effect on the Gram‐negative bacteria E. coli and Salmonellae, which are difficult to control with other natural preservatives. ɛ‐Polylysine has already been used generally as a food additive in Japan, Korea and other part of world. In the United States, FDA has recognized the polylysine as a GRAS material. Considered the positive results obtained in the study, this compound could be used for the production of antimicrobial biofilms, applied as separator slices in the loaf bread production, to prevent the growth of the mycotoxigenic fungi A. parasiticus and P. expansum, contributing to reduce the use of the synthetically preservatives in bakery industry and also of the negative impact that these compounds could generate on the health of the end users.